O17. The Groote Schuur Radiotherapy time machine: Creating the future you would like to see. (September 2016) - Burger, H.; Parkes, J.; Youngleson, S.M.; Nel, T.; Botha, J.; Bruwer, J.; Joubert, N.
Abstract : Introduction: It is estimated that South Africa (SA) will require 56 additional linear accelerators by 2020. Linacs are considered a scarce resource and optimal use is essential. Many state run facilities in SA make use of historic staffing models, not taking into account changes in techniques or alternative work practices. Attempts to implement alternative staffing models can result in resistance as staff struggle to link work practice with patient numbers. A visual tool was developed to assist staff in assessing alternative practices and linking the staffing models to the number of patients treated. Materials and Methods: A magnetic game board called the GSH Time Machine was developed in the form of a 12 hour "clock face", allowing visualisation of staffing activities on the inside of the clock face, linked to the treatment slots utilised on the outside of the clock face. A workshop was held with Radiotherapy staff members to develop different staffing boards. Each team was allowed to implement their board on their unit. The impact was monitored from May 2015 to June 2016 and compared to the historic mean data for slot utilization and number of new patients treated per month. Results: Staff found the game board fun, and were willing to adopt new strategies. The three units responded differently to the intervention, with one linac showing a statistically significant increase in both indices. The second linac initially showed a decrease in new patients treated as a result of an incorrect application of the board. Once corrected, the unit showed an increase in both indices. The Co-60 unit remained stable as designed. Conclusion: The GSH Time Machine is a useful lean management tool to allow for visualisation of the impact of staffing practices.